Implementation of community dental and oral health care before COVID-19 pandemic to new normal period at Public Health Care - Hertanto, Muhamad Tio Dwi; Hidayat, Wahyu; Suryanti, Netty (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Dental health services at primary health care (PHC) are the first and foremost effort to overcome dental health problems in the community, consisting of Individual Health Care (IHC), Community Dental Health Care (CDHC), and School Dental Health Care (SDHC). The COVID-19 pandemic in Indonesia has hampered dental health services at PHC. This study aims to describe the implementation of dental health Care at the PHC from before COVID-19 pandemic to the new normal adaptation period. Methods: Descriptive cross-sectional study conducted from January to February 2022. The sample consisted of 15 PHC in Bandung, West Java, Indonesia, interviewing dentists and doing a checklist on the rubric for each activity implementation. Data processing by the percentage of implementation. Results: The implementation of promotive before the pandemic was 100%, when the pandemic decreased and increased again by almost 100% during the new normal adaptation period. Before the pandemic, most preventive measures were just 56%. During the pandemic, there were nearly no activities, and during the new normal adaptation period, there was an increase, but the percentage was low. The curative implementation before the Pandemic was almost 100% implemented. At the beginning of the pandemic, the implementation decreased, but 100% was carried out for counseling and referrals. Most care has been implemented up to 100% during the adaptation period. The implementation of rehabilitation during the pandemic period was still low (40%). At the beginning of the pandemic 13%, and during the adaptation period, there was an increase according to the pandemic period (33%). Conclusion: Before the pandemic, promotive and curative services had been maximized, while preventive and rehabilitative services still needed to be maximized. During the beginning of the pandemic, almost all services stopped. During the new normal adaptation period, all services have increased again compared to the initial period of the pandemic. Keywords: dental; oral health; primary health care; COVID-19; pandemic